2022
DOI: 10.3390/ijms23126386
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9-Directed Gene Trap Constitutes a Selection System for Corrected BCR/ABL Leukemic Cells in CML

Abstract: Chronic myeloid leukaemia (CML) is a haematological neoplasm driven by the BCR/ABL fusion oncogene. The monogenic aspect of the disease and the feasibility of ex vivo therapies in haematological disorders make CML an excellent candidate for gene therapy strategies. The ability to abolish any coding sequence by CRISPR-Cas9 nucleases offers a powerful therapeutic opportunity to CML patients. However, a definitive cure can only be achieved when only CRISPR-edited cells are selected. A gene-trapping approach combi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…However, these risks may be addressed with autologous transplantation of gene-edited HSCs. The CRISPR/Cas9 system has been demonstrated to effectively disrupt BCR::ABL1 at the genomic level leading to leukemia cell death in vitro and in vivo with no off-target effects [ 126 , 127 , 128 , 129 ]. Despite high gene-editing efficiency using the CRISPR/Cas9 system, a major barrier to curative gene therapy in CML is the presence of unedited cells that have the potential to initiate relapse after transplantation [ 127 ].…”
Section: Tki Treatment Strategies In the Clinicmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these risks may be addressed with autologous transplantation of gene-edited HSCs. The CRISPR/Cas9 system has been demonstrated to effectively disrupt BCR::ABL1 at the genomic level leading to leukemia cell death in vitro and in vivo with no off-target effects [ 126 , 127 , 128 , 129 ]. Despite high gene-editing efficiency using the CRISPR/Cas9 system, a major barrier to curative gene therapy in CML is the presence of unedited cells that have the potential to initiate relapse after transplantation [ 127 ].…”
Section: Tki Treatment Strategies In the Clinicmentioning
confidence: 99%
“…The CRISPR/Cas9 system has been demonstrated to effectively disrupt BCR::ABL1 at the genomic level leading to leukemia cell death in vitro and in vivo with no off-target effects [ 126 , 127 , 128 , 129 ]. Despite high gene-editing efficiency using the CRISPR/Cas9 system, a major barrier to curative gene therapy in CML is the presence of unedited cells that have the potential to initiate relapse after transplantation [ 127 ]. To overcome this, a proof-of-concept study described the efficacy of a CRISPR-gene trapping strategy that would allow for CRISPR-edited cells to be selected before transplantation [ 127 ].…”
Section: Tki Treatment Strategies In the Clinicmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, CRISPR-Cas systems have been used for cancer gene therapy. Strategies have included insertion of suicide genes(11), targeting mutations in oncogenic driver genes that contain PAM sites(12, 13), unique sequences in oncoviruses such as E6 and E7(14), and fusion oncogenes(15, 16). We recently reported that somatic single base substitutions (SBS) forming novel PAM sites specific to cancer cells are targetable by CRISPR/Cas9.…”
Section: Introductionmentioning
confidence: 99%
“…Vuelta and co-workers [ 4 ] presented a gene-trapping approach combined with CRISPR technology as an ideal methodology to increase the selection of CRISPR-edited cells as a potential approach for the treatment of BCR/ABL-driven chronic myelogenous leukemia (CML). Strikingly, both in vitro and in vivo experiments demonstrated a significant reduction in CML tumor cell proliferation and tumor growth, thus providing a proof-of-concept for the therapeutic potential of a CRISPR-trap system as a novel strategy for gene elimination in hematological neoplasms.…”
mentioning
confidence: 99%